2020
DOI: 10.3390/molecules25245995
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid Delivery by Solid Lipid Nanoparticles Containing Switchable Lipids: Plasmid DNA vs. Messenger RNA

Abstract: The development of safe and effective nucleic acid delivery systems remains a challenge, with solid lipid nanoparticle (SLN)-based vectors as one of the most studied systems. In this work, different SLNs were developed, by combination of cationic and ionizable lipids, for delivery of mRNA and pDNA. The influence of formulation factors on transfection efficacy, protein expression and intracellular disposition of the nucleic acid was evaluated in human retinal pigment epithelial cells (ARPE-19) and human embryon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In the last decades, considerable advances have been made in the conception of nucleic acid-based delivery systems to overcome the major drawbacks of payload delivery to eukaryotic cells, namely, cellular uptake/internalization, endosomal escape, targeting a specific subcellular compartment, and ultimately, the induction of therapeutic action [19,[21][22][23][24]. In line with this aim, micelles, polymers, lipid-and peptide-based nanoparticles are among the most studied systems for gene release [25][26][27][28]. In particular, cell-penetrating peptides (CPP) offer exceptional properties to be explored as gene delivery vehicles for successful gene therapy [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, considerable advances have been made in the conception of nucleic acid-based delivery systems to overcome the major drawbacks of payload delivery to eukaryotic cells, namely, cellular uptake/internalization, endosomal escape, targeting a specific subcellular compartment, and ultimately, the induction of therapeutic action [19,[21][22][23][24]. In line with this aim, micelles, polymers, lipid-and peptide-based nanoparticles are among the most studied systems for gene release [25][26][27][28]. In particular, cell-penetrating peptides (CPP) offer exceptional properties to be explored as gene delivery vehicles for successful gene therapy [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages of using pDNA versus mRNA include the possibility to obtain abundant purified pDNA easily and economically, and the opportunity to perform repeated administrations without triggering an immune response [ 30 ]. Nevertheless, pDNA transfection is more difficult than that of mRNA, mainly due to the nuclear entry barrier [ 25 ]. In earlier studies, our research group has demonstrated the potential of SLN-based vectors-mediated pDNA delivery encoding α-Gal A to produce the enzyme in a liver-derived cell line (Hep G2) [ 26 ] and in a cell model of FD [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase of α-Gal A activity observed after IV administration to mice of either the naked pDNA or the SLN-based vector, demonstrate their ability to circulate in the bloodstream and reach the tissues. Contrary to the naked pDNA, the SLN-based vector provides a higher stability to the pDNA and facilitates its internalization by the cells, which may explain the higher efficacy [ 21 , 25 , 26 , 27 , 28 ]. After the administration of the SLN-based vector once a week for three weeks, heart and kidney (the most important target organs) were the tissues where the greatest difference in α-Gal A activity between the naked pDNA and the SLN-based vector was detected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLN EE were elaborated as previously reported [33], with the solid lipid Precirol ® ATO 5 and the cationic lipid DOTAP, stabilized by the surfactant Tween 80. Briefly, SLN EE were obtained by the sonication (Branson Sonifier 250, Danbury) of the organic phase (Precirol ® ATO 5 dissolved in dichloromethane 5% w/v) in the aqueous phase, containing the cationic lipid DOTAP (0.4% w/v) and Tween 80 (0.1% w/v).…”
Section: Formulation Of Slns and Vectorsmentioning
confidence: 99%